Epidemiology and psychosocial assessment of COVID-19 among workersof the Nigeria Centre for Disease Control infected with COVID-19 - Fatima Saleh; David Idowu Olatunji; Ehichioya Ofeimun; Evaezi Okpokoro; Emily Crawford; Mahmood Dalhat; Ehimario Igumbor; Sunday Eziechina; Stella Inweregbu; Chinwe Lucia Ochu; Ihekweazu Chikwe (AOSIS, 2023)
Background. COVID-19 is a global health crisis. By 2021, Nigeria had 230,000 cases. As the national public health institute, NCDC leads the COVID-19 response. Due to constant contact with infected patients, agency employees are at high-risk. Here, we describe the transmission and psychosocial effects of COVID-19 among infected NCDC workers as a learning curve for minimizing occupational transmission among frontline public health workers in future outbreaks. Methods. We approved and enrolled all NCDC COVID-19-infected personnel from November to December 2020. We collected data using SurveyMonkey. STATA 14 analyzed the data. Results. 172 of 300 afflicted NCDC staff participated in this study. One-third were between 30 and 39; most were male (104, 60.5%). Most participants worked in the lab (30%) or surveillance (24%). Only 19% (33/172) of participants confirmed pandemic deployment. Most reported interaction with a confirmed case (112/65.1%). Most people (78, 45.3%) felt unhappy when diagnosed. Anger, worry, and low motivation also ranked high (19). The majority reported adequate financial, moral, or psychosocial assistance (26, 70.6%). Conclusions. NCDC staff had a high SARS-CoV-2 infection rate and emotional damage. We urge stricter infection control methods when sending staff for outbreaks response to prevent additional transmission, as well as ongoing psychosocial and economic assistance for afflicted workers.